(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Examines the processes occurring in national economy in the modern period in connection with the development of a fundamentally new social institution, namely the welfare state. The arguments about the need to introduce along with market management mechanism updates the source base of its social immunization. Based on the study of the realities of the social recovery of the developed countries proved that in the conditions of resource limitation of their achievement was the result of harnessing the potential of social innovation. Critically evaluated a range of approaches to engage in scientific and practical usage of the concepts «innovation» and «innovation introduction process». Guided by the developments of foreign scientists and the results of processing the semantic differences slovotsky affixes of the words «innovation» and «innovation introduction process» proposed to qualify the innovation as a result of enhancement of any existing object. It was found that for playback of the past in the present and future applies such a thing as tradition, which is one of the most effective mechanisms of adaptation of human communities to the changing environment through the regulation of institutions and institutions. Proven that innovations occur and are implemented by modernisation tradition. The essence of social innovation introduction process as a process associated with the formation of the construct of appropriate innovations and their implementation in social practice with the achievement of acceptable social result. To provide controlled social innovation introduction process invited to consider this process as a complex construct of the three phases. Under the proposed concept of a managed social innovation introduction process in the first phase are manifested in social institutions that require change; the second is formed a construct of social innovation based on social abnormal deviations from the implemented improvements in the last cycle of social innovation introduction process; the third monitoring (audit) and the determination of the degree of coincidence of the real impact on social change with the project. The specifics of the managed social innovation introduction process is to avoid the «catch-up» type of social innovation that is not able to achieve civilized living standards in the short term, and transition to the strategy of «secured advance» or «from the future». Focuses on the fact that the logic of the process of social innovation introduction process should be such that only from the standpoint of a new, more perfect, in the extent made to change the social architecture of companies.